(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Layek U, Das A, Das U. 2022. Floral biology, floral volatile organic compounds and floral visitors of Chromolaena odorata, an invasive alien species in West Bengal, India. Biodiversitas 23: 2118-2129. Chromolaena odorata (L.) R.M. King & H. Rob. is a fast-growing weed native to the Neotropics and introduced in several regions of Africa, the Pacific Islands, and Southeast Asia, including West Bengal in India. It is one of the world’s most widespread and troublesome invasive alien plant species (IAPS) that severely infest natural habitats and crop fields. However, extensive data documents about the reproductive ecology are unknown, especially within West Bengal. This study assesses the floral biology, floral volatile organic compounds (VOCs), and floral visitors of the weed. The weed species flowers from October to January. Florets are white to purple, with short, narrow corolla tubes and deep-seated nectar. Abundant VOCs are benzyl stearate, 2,4-decadienal, n-hexadecanoic acid, 1-hexyl-2-nitrocyclohexane, and o-decyl hydroxylamine. Flower heads were visited by numerous insect groups, though the diversity of Lepidoptera (mainly butterflies) was higher than the other insect orders. The weed is pollinated by diverse insect groups (e.g., butterflies, flies, honeybees, leafcutter bees, solitary bees, and wasps). However, vital pollination services to the weed were provided by butterflies (based on the ‘approximate pollination value’). Our findings may conclude that the clustered capitula, longer stigmatic receptivity, and broad array of pollinators resulted in too much fruit set. It is one of the critical factors that support the high growth rate and invasive nature of the weed in dry habitats.